Does More Respect from Leaders Postpone the Desire to Retire? Understanding the Mechanisms of Retirement Decision-Making - Wöhrmann, Anne M.; Fasbender, Ulrike; Deller, Jürgen (Frontiers in Psychology, 2017)
The demographic trends (i.e., low birth rates and increasing longevity) pose challenges with regard to the increase of the average employee age along with a lack of skilled personnel on the labor market. Society, organizations and individuals are confronted with the question on how to prolong working lives in the future. Based on socioemotional selectivity theory, the purpose of this study was to investigate the relationship between respectful leadership and older workers’ desired retirement age. In particular, we took a closer look at job satisfaction, subjective health, and work-to-private life conflict as underlying mechanisms. Further, we tested for the moderating role of occupational self-efficacy as an auxiliary condition for the assumed relationships of respectful leadership. We tested our hypothesized model using data from 1,130 blue and white collar workers aged 45 to 65. The results of structural equation modeling indicated that respectful leadership was positively related to older workers’ desired retirement age and that this relationship was mediated by subjective health and work-to-private life conflict but not by job satisfaction. The findings add to the literature on resources in retirement decision-making; notably they highlight the importance of leadership behavior for older workers’ motivation and socioemotional needs.